An Ethnomathematical Exploration of Geometric Transformations in Torajan Paruki Woven Fabrics - Muhammad Nurhusain; Nur Asrawati; Suri Lembang (Universitas Sulawesi Barat, 2026)
This study explored the ethnomathematical aspects of Paruki woven fabrics preserved at the La Galigo Museum by identifying geometric transformations embedded in their motifs and discussing their pedagogical implications for teaching transformation geometry. Paruki woven fabric is a traditional Torajan textile historically associated with ceremonial practices, including Rambu Solo'. The study employed an exploratory qualitative design informed by ethnographic principles, using artifact observation, semi-structured interviews with museum professionals, and document analysis. The findings revealed that the motifs embodied translation, reflection, rotation, and proportional scaling. Translation was the dominant transformation, while reflection and rotation were observed in symmetrical and repetitive motif arrangements, and proportional scaling was identified through similar geometric figures of different sizes. These mathematical patterns were interpreted alongside their cultural meanings, demonstrating the value of Paruki woven fabrics as culturally meaningful contexts for learning transformation geometry. This study extends ethnomathematics research by linking Torajan textile motifs with transformation geometry concepts and highlighting their potential to support culturally responsive mathematics education.